STUDI PENYEDIAAN NANOKRISTAL SELULOSA DARI TANDAN KOSONG SAWIT (TKS) - Fenny Aulia (USU, 2013)
Isolation and characterization cellulose nanocrystal of alpha cellulose from Palm Empty Fruit Bunch (EFB) have been performed. Oil Palm Empty Fruit Bunch (EFB) was delignificated with 3,5% HNO3 and NaNO2, precipitated with17.5% NaOH, bleaching process with 10% H2O2. Nanocrystal obtained through the hydrolysis of alpha cellulose using 45% H2SO4. Nanocrystal surface structures cellulose analyzed by Scanning Electron Microscopy (SEM) and the results show that the resulting cellulose Nanocrystal size 79 nm. Analysis of thermal degradation using Thermal Gravimetric Analysis (TGA) showed that cellulose Nanocrystal starting temperature of 160oC decomposes. It shows the process of cellulose Nanocrystal isolation of alpha cellulose has occurred. Keywords: empty fruit bunches palm, hydrolisys, nanocrystal cellulose